MOTIVASI KUNJUNGAN WISATAWAN KE OBJEK WISATA LAWANG PARK KABUPATEN AGAM SUMATERA BARAT - Naufal Munadi; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this research is to know the motivation of tourist when visiting to Lawang Park destination, Agam Regency, West Sumatera. This research uses a quantitative method with a descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The key informants in this research were tourists visiting the Lawang Park destination, Agam Regency. In research, the data collection techniques used were questionnaire, observation and documentation. Based on the results of the study, it can be concluded that tourists visiting the Lawang Park Destination stated agree from the 4 indicators of tourist motivation that have referred to the grand theory used. Keywords:  Motivation, tourist, destination